INVESTIGATION OF THE EFFECT OF ORGANIZATIONAL CULTURE ON PERCEIVED ORGANIZATIONAL SUPPORT AND INTERNAL ENTREPRENEURSHIP INTENTION: EXAMINATION OF A PUBLIC INSTITUTION (Third Sector Social Economic Review, 2024)
Organizational culture is a set of values that are created by institutions and hold organizations together, and that develop and change throughout the period they are established. The impact of organizational culture, which has such importance, on employee behavior and success cannot be ignored. In order for an organization to continue, employees must feel supported, appreciated, and sincerely met by the organization in terms of their effective and productive work. Employees will respond to this supportive behavior with a sense of belonging and identification that increases their participation in the organization's activities, their willingness to achieve the organization's goals, and their commitment to the organization, with an emotional attachment. As a sub-branch of entrepreneurship, intrapreneurship refers to entrepreneurial behaviors within the organization. In other words, intrapreneurship can be expressed as the ability to embody an innovative idea in an ongoing organization and turn it into feasible projects, making free decisions, and exhibiting behaviors outside of routine. In this study, it is aimed to show whether the organizational culture, including subscales, has an effect on perceived organizational support and intrapreneurial behavior on 250 employees working in the central units of the Ministry of Treasury and Finance in Ankara, and if so, in what direction and how. A 4-part survey with questions regarding the demographic characteristics of the participants was used as the data collection technique. The data was obtained with analytical methods according to the quantitative research methodology and the obtained data was analyzed with special programs. As a result of the study, it was seen that the perspectives of the employees on the organizational culture significantly affected the perceived organizational support and intrapreneurship behaviors and these three scales were statistically significant and related to each other. It was seen that the organizational culture positively and statistically significantly affected the perceived organizational support and intrapreneurship. In other words, the increase in the organizational culture among the participants in the study provided an increase in the perceived organizational support and intrapreneurship. On the other hand, it was seen that some organizational culture subscales negatively and insignificantly affected the perceived organizational support and intrapreneurship (consistency and mission subscales affected the perceived organizational support, and the closeness of fit subscale affected the intrapreneurship).
Keywords: Organizational Culture; Perceived Organizational Support; Internal Entrepreneurship